Foliar sampling guidelines for different aged Acacia mangium plantations in Peninsular Malaysia - Nik Ab. Majid, Nik Muhamad; Alias, Mohamad Azani; Paudyal, Bimal Keshari (Forest Research Institute Malaysia, 1998)
Foliar analysis is a useful tool for evaluating the nutritional status of a crop. There are, however, no guidelines for foliar sampling of Acacia mangium plantations in Peninsular Malaysia. This study was thus aimed to determine the best time for foliar sampling in Acacia mangium plantation. The study was conducted in Kemasul Forest Reserve, Pahang. Foliar samples were collected monthly from Acacia mangium stands of five different ages over a period of one year. The results show that foliar sampling in Acacia mangium stands should be performed as follows: for one-year-old stand in January-March and June-July; for two-year-old stand in December-January and June-July; for three-year-old stand in June-July; for four-year-old stand in February-March and June-July; for six-year-old stand in February-March. In general, July is the best time for foliar sampling of one- to four-year-old stands whereas February-March would be the best time for six-year-old stands. The results are based on the fact that foliar nutrients are generally constant over these periods.